DESAIN SISTEM INFORMASI REKAM MEDIS DALAM MENUNJANG PELAPORAN SENSUS HARIAN RAWAT INAP DENGAN V-MODEL - Luvi Luthfia Diranti; Yuda Syahidin; Yuyun Yunengsih (POLITEKNIK PIKSI GANESHA, 2023)
This study aims to design a daily inpatient census information system. The research method was carried out using a qualitative descriptive method with a design model, while the data collection techniques were observation, interviews and literature study. Based on the research conducted, the management of daily inpatient census data has not been computerized. Therefore, a new system was created using Microsoft Visual Studio 2013, with My Sql database, using the v-modell software development model, so that the user, in this case, is an officer, only simply inputs data in the form provided and the data can be directly processed. so that the desired output results are obtained. The suggestions given are: 1) to make a computerized barber johnson graphic information system, which can reduce weaknesses during manual system implementation, and 2) it is necessary to plan maintenance and care for the continuous development of the system